Molecular techniques in transfusion management of patients with autoimmune hemolytic anemia - Fernandez Bolivar, Lizette (2025)
Autoimmune hemolytic anemia (AIHA) is a rare disease that complicates pre-transfusion tests due to the presence of autoantibodies interfering with conventional serological techniques. This increases the risk of alloimmunization and hinders the selection of compatible units, particularly in multi-transfused patients. This article reviews the use of molecular techniques, such as red blood cell genotyping, to improve transfusion safety in AIHA patients. Data sources such as PubMed, Cochrane, Medline, and Scielo were reviewed to identify relevant studies published between 2013 and 2024. Molecular techniques provide faster and more precise typing, overcoming serological interferences, but face challenges like high costs and limited infrastructure in countries like Peru. The centralization of molecular immunohematology laboratories is proposed as a cost effective solution to ensure equitable access. These tools represent a significant step towards safer and more efficient transfusion practices.